Evidence for Possible New Subglacial Lakes along a Radar Transect Crossing the Belgica Highlands and the Concordia Trench - Forieri, A.; Tabacco, I. E.; Cafarella, L.; Urbini, S.; Bianchi, C.; Zirizzotti, A. (Terra Antartica Publication, 2008)
Subglacial lakes are of great interest to the scientific community, and about 190 lakes have been identified in Antarctica and catalogued (Siegert et al., 2005; Cafarella et al., 2006; Popov & Masolov, 2007). We report on the possible existence of 5 new subglacial lakes in the area between the Belgica HighLands and the Concordia Trench. Analysis of radar data collected during the 2003 Antarctic field survey reveals particularly strong radar echoes coming from the subglacial interface. As radar surveys are only one of the methods used to identify subglacial lakes, the presence of these 5 new lakes must be discussed and confirmed through other geophysical investigations. Published 209-212 3.8. Geofisica per l'ambiente N/A or not JCR partially_open